Comparing oral health-related quality of life, oral function and orofacial aesthetics among a group of adolescents with and without malocclusions. (17th February 2022) - Sörensen, Caroline; Lemberger, Mathias; Larsson, Pernilla; Pegelow, Marie
Abstract: Objective: The aim was to analyze how malocclusion relates to perception of oral health-related quality of life (OHRQOL), oral function and orofacial aesthetics among a group of adolescents in Sweden. Material and methods: Thirty patients with a need for orthodontic treatment (IOTN-DHC grade 4 and 5) and 30 patients with normal occlusion (IOTN-DHC grade 1), aged 13–17 years, were included in the study. A questionnaire containing three parts was used; The Oral Health Impact Profile (OHIP-S14), Jaw Functional Limitational scale (JFLS-20) and Orofacial Aesthetic scale (OES). Malocclusions, orthodontic treatment need and confounders, such as earlier dental treatment and temporomandibular disorders, were registered. Results: Adolescents with malocclusions were more often embarrassed by their mouth and teeth compared to controls ( p < .05). Aesthetically, adolescents with malocclusions were more negatively affected by the appearance of the mouth and teeth as well as the over-all facial appearance ( p < .05). Conclusions: Malocclusions clearly affects the adolescents with need for orthodontic treatment in this study. It influences their OHRQOL in the psychosocial impact dimension. Aesthetically they perceive their oral and facial appearance as worse compared to controls. Although embarrassed and unpleased with their oral appearance they still rate themselves as having a good oral health with low jaw function limitations.